Evaluasi Profil Penyimpanan Obat Di Rumah Sakit Islam Faisal Kota Makassar Terhadap Pelayanan Kefarmasian - Nurlina Nurlina; Andi Maulana Kamri; Andi Nadilla Arfah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Drug storage is a method of maintaining pharmaceutical supplies aimed at maintaining the quality of a drug. Improper storage of drugs can cause drug damage, be ineffective in treatment, and will be a loss to the hospital. The purpose of this study was to determine the profile of drug storage in the Pharmacy Installation of Faisal Islamic Hospital, Makassar City. This research is a descriptive qualitative research in which the data is obtained from in-depth interviews, direct observation, document review, and checking of the condition of drug stability in the Pharmacy Installation. The results showed that the facilities and infrastructure only reached 81% compliance, were some shortcomings such as moldy walls and no double doors. Preparation of drugs in the storage warehouse of the Pharmacy Installation of the Faisal Islamic Hospital reached 100% carried out according to applicable standards. The recording of the card stock has been carried out well with a conformity percentage of 100%. Checking the condition of drugs such as color, odor, shape, clarity, and packaging is done properly every day, checking expiration every month. This study concludes that facilities and infrastructure are one of the supports to improve pharmaceutical services in hospitals in terms of storage.